Action and Interaction: active methodologies in the teaching of History in Secondary Education - de la Guardia Montesdeoca, Gisela (Clio. History and History Teaching, 2022)
By active methodologies we understand those didactic proposals that revolve around the role of students as generators of knowledge and that build their learning based on interaction with the group. This approach constitutes the raison d'être of this work where Action and Interaction become an exalted cry that calls for change from the classroom itself.